Changes on the 21st Century Labour Market and the Profile of the “Employee of The Future” in the Opinion of University Students and Graduates – The Representatives of Generation “Z” in Poland - Magdalena RĘKAS (Communications of International Proceedings, 2020)
The 21st century is characterized by the extremely dynamic socio-economic changes which affect the functioning of organizations and entire markets, in particular the labour market. Numerous trends can be observed which radically change the sphere of work and employment, i.e.: work globalization, automation and robotisation, industry 4.0, technological innovations, rapid urbanization, negative demographic changes, the increasing importance of flexible employment forms, the growing scale of self-employment and remote work, the implementation of Work Life Balance model, creative work, agile organizations and teams, teal organizations, etc. To a much greater extent, the appropriate human capital becomes the source of competitive advantage and business success. Organizations need motivated and committed employees presenting appropriate and diverse competences, drawing conclusions from the surrounding reality, capable of adapting to changes, creating innovations, developing products and services suitable for the increasingly diverse, demanding and knowledgeable customers. Generation “Z” is entering the labour market in growing numbers, having different characteristics from previous generations and creating further changes in employment models and work organization. The article discusses the results of a pilot study aimed at answering two research questions: What is the approach of university students and graduates representing generation “Z” in Poland to the changes on the 21st century labour market? What is the profile of the “employee of the future” in the opinion of this generation? Based on the analysis of Polish and foreign literature, the article presents a general description of generation “Z” representatives, including their values, needs and motivations as well as their behaviour on the labour market. The research findings describe the profile of the “employee of the future”, including the expectations and characteristics of an employee representing generation “Z” university graduate, which should constitute an important element in developing a correct HR policy in an enterprise.
Keywords: labour market; factors of the labour market changes; generation Z; profile of the employee of the future